Efektifitas Pemberian Tablet Curcuma, Putih Telur, dan Susu terhadap Asupan dan Berat Badan Pasien Tuberkulosis Dengan dan Tanpa Komorbiditas Effectiveness of Supplementation of Curcuma, Egg White, and Milk Tablets on Intake and Body Weight of Tuberculosis Patients With and Without Comorbidity - Nadiyah, Nadiyah Nadiyah; Cahyani, Cahyani Cahyani; Novianti, Anugrah Anugrah (Jurnal Nutrire Diaita (Ilmu Gizi), 2020)
Indonesia has the second highest pulmonary TB (tuberculosis) cases after India. TB problem is included in three national health priorities in Indonesia besides stunting and immunization.  Jakarta is the province with the second largest number of pulmonary TB patients after West Java. Curcuma tablet is indicated to increase appetite. Milk and white egg as protein sources are high energy natural sources that are expected  to improve nutritional status of TB patients either with or without comorbidities. The objective of this study was to assess the effectiveness of supplementation of curcuma, white egg and milk to energy and protein intake and weight among pulmonary TB patients with and without comorbidities in Regional General Hospital Tarakan Jakarta. A One group pre and post test design was carried out with 33 samples of pulmonary TB patients who meet inclusion criteria. Energy and protein intake were measured by food recall and food weighing. Multivariate analysis of variance (manova) was used to determine the effectiveness of supplementation of curcuma, white egg and milk to energy and protein intake and weight between pulmonary TB patients with and without comorbidities. The result showed that there was no significant difference inincreasing energy and protein intake and weight after supplementation of curcuma, white egg and milk between pulmonary TB patients with and without comorbidities (p >0.05). There is no effect of comorbidities to increase of weight, energy and protein intake among pulmonary TB patients after supplementation of curcuma, white egg and milk. Keywords : curcuma, intake, weight, pulmonary TB, comorbidities Indonesia adalah negara dengan kasus TB terbanyak kedua setelah India.Masalah TB termasuk dalam tiga prioritas kesehatan nasional disamping stunting dan imunisasi. Propinsi DKI Jakarta adalah propinsi dengan TB paru tertinggi kedua setelah Jawa Barat. Tablet curcuma diindikasikan untuk menambah nafsu makan. Susu dan putih telur sebagai sumber protein merupakan makanan alami tinggi kalori yang diharapkan dapat meningkatkan status gizi penderita TB paru baik dengan ataupun tanpa komorbiditas.Tujuan penelitian ini adalah menjelaskan efektifitas pemberian tablet curcuma, putih telur, dan susu  terhadap asupan (energi dan protein)dan berat badan pada penderita tuberkulosis paru berdasarkan ada dan tidaknya komorbiditasdi RSUD Tarakan Jakarta. Penelitian ini menggunakan desain studi eksperimen one group pre and post test design. Sampel adalah pasien yang didiagnosis TB paru, yang dirawat di ruang rawat inap kelas III RSUD Tarakan Jakarta, yang memenuhi kriteria inklusi, yaitu sebanyak 33 sampel. Pengukuran asupan energi dan protein menggunakan metode food recall dan food weighing.Analisis data menggunakan uji multivariate analysis of variance (manova). Hasil penelitian menunjukkan tidak terdapat perbedaan peningkatan asupan energi, protein dan berat badan setelah perlakuan pemberian tablet curcuma, putih telur dan susu antara penderita TB paru tanpa komorbiditas dan penderita TB paru dengan komorbiditas (p>0,05).Tidak ada efek komorbiditas terhadap kenaikan berat badan dan asupan energi serta asupan protein pada penderita TB setelah diberikan intervensi tablet curcuma, putih telur dan susu.